Controlling shape and position of vascular formation in engineered tissues by arbitrary assembly of endothelial cells. (6th November 2015) - Takehara, Hiroaki; Sakaguchi, Katsuhisa; Kuroda, Masatoshi; Muraoka, Megumi; Itoga, Kazuyoshi; Okano, Teruo; Shimizu, Tatsuya
Abstract: Cellular self-assembly based on cell-to-cell communication is a well-known tissue organizing process in living bodies. Hence, integrating cellular self-assembly processes into tissue engineering is a promising approach to fabricate well-organized functional tissues. In this research, we investigated the capability of endothelial cells (ECs) to control shape and position of vascular formation using arbitral-assembling techniques in three-dimensional engineered tissues. To quantify the degree of migration of ECs in endothelial network formation, image correlation analysis was conducted. Positive correlation between the original positions of arbitrarily assembled ECs and the positions of formed endothelial networks indicated the potential for controlling shape and position of vascular formations in engineered tissues. To demonstrate the feasibility of controlling vascular formations, engineered tissues with vascular networks in triangle and circle patterns were made. The technique reported here employs cellular self-assembly for tissue engineering and is expected to provide fundamental beneficial methods to supply various functional tissues for drug screening and regenerative medicine.